Effect of phosphatidylcholine regioisomerism on lateral segregation of milk sphingomyelin in bilayer membranes - Sazzad; Md Abdullah Al; Lönnfors, Max; Yang, Baoru (Elsevier BV, 2025)
Milk fat globule membrane (MFGM) promotes the lateral phase separation of milk lipids and stabilizes the fat globules in milk. The composition and structures of lipids have a significant impact on physicochemical properties of MFGM, which in turn influences the digestion and absorption of milk lipids. Phospholipids (PL), sphingolipids, and cholesterol are the major lipid constituents of MFGM. While the effects of the head-group and structure of the fatty acids (FAs) on membrane properties are commonly studied, little is known on the impact of PL regioisomerism. The present study investigated the impact of phosphatidylcholine (PC) regioisomerism on lateral segregation of milk-sphingomyelin (milk-SM) as well as the influence on the interaction of milk-SM with ceramide and cholesterol in simulated membrane systems. The regioisomer pairs of four molecular species PC 16:0/18:1n-9, PC 16:0/18:2n-6, PC 16:0/18:3n-3, and PC 16:0/20:4n-6 were included in this study. The lateral segregation was determined using lifetime analysis of trans-parinaric acid (tPA) fluorescence. Thermostability of the domains was detected using steady-state anisotropy of tPA. Our results demonstrated a clear impact of PC regioisomerism on membrane properties. PC regioisomers having the unsaturated FAs at the sn-2 position enhanced the lateral segregation of milk-SM with and without the presence of ceramide and cholesterol compared to the regioiosmers having 16:0 at the sn-2 position. Furthermore, the characteristics i. e. the acyl chain length and degree of unsaturation of sn-2 FA of the PCs had a major impact on the milk-SM gel phase and the intermolecular forces between milk-SM and ceramide/cholesterol. This work is the first investigation showing the effect of PL regioisomerism on milk-SM domains, which might have significant influence on functional properties of MFGM.